2021
DOI: 10.1002/wnan.1753
|View full text |Cite
|
Sign up to set email alerts
|

Multimodules integrated functional DNA nanomaterials for intelligent drug delivery

Abstract: Deoxyribonucleic acid (DNA) has been an emerging building block to construct functional biomaterials. Due to their programmable sequences and rich responsiveness, DNA has attracted rising attention in the construction of intelligent nanomaterials with predicable nanostructure and adjustable functions, which has shown great potential in drug delivery. On the one hand, the DNA sequences with molecule recognition, responsiveness, and therapeutic efficacy can be easily integrated to the framework of DNA nanomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…In addition, the application of DNA nanomaterials in biosensors can be expanded by modifying DNA with fluorescent groups and designing stimulus response structures such as DNAzyme, Gquadruplex, and ATP aptamer. 52 In addition, studies have shown that rolling circle amplification reaction, DNA hybridization chain reaction, and DNA catalytic hairpin self-assembly have great potential in realizing signal amplification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the application of DNA nanomaterials in biosensors can be expanded by modifying DNA with fluorescent groups and designing stimulus response structures such as DNAzyme, Gquadruplex, and ATP aptamer. 52 In addition, studies have shown that rolling circle amplification reaction, DNA hybridization chain reaction, and DNA catalytic hairpin self-assembly have great potential in realizing signal amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by integrating with smart nanostructures, more multi-functional DNA smart drug delivery nanocomplexes with dynamic response are expected to be developed, which greatly promotes the development of precision medicine. In addition, the application of DNA nanomaterials in biosensors can be expanded by modifying DNA with fluorescent groups and designing stimulus response structures such as DNAzyme, G-quadruplex, and ATP aptamer . In addition, studies have shown that rolling circle amplification reaction, DNA hybridization chain reaction, and DNA catalytic hairpin self-assembly have great potential in realizing signal amplification …”
Section: Discussionmentioning
confidence: 99%
“…[20,35] Aptamer is a type of single-stranded DNA with a specific sequence that can fold into highly-ordered structure. [36] Aptamers can recognize specific biomolecules, for example, Sgc8 aptamer specifically binds with the overexpressed protein tyrosine kinase 7 (PTK7) on cancer cell surfaces [37,38] and AS1411 aptamer specifically targets nucleolin. [39][40][41][42] The aptamer sequences can be introduced into two kinds of DNA nanogels by encoding the circle template [19,43] or adding to the DNA building blocks, [12] thereby assisting nanogel to achieve active targeting.…”
Section: Construction Of Targeted Dna Nanogelmentioning
confidence: 99%
“…Affinity chromatography is an efficient protein separation method based on the interaction between specific immobilized ligands and target proteins, and nucleic-acid aptamers are promising affinity ligands in affinity chromatography. , dsDNA is a natural substrate for the MutY protein. Compared with the aptamers that require screening and antibodies with long and expensive preparation cycles, dsDNA is merited with adjustable sequences, good stability in solution, and less difficulty in production, which makes it a favorable candidate for functional modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the aptamers that require screening and antibodies with long and expensive preparation cycles, dsDNA is merited with adjustable sequences, good stability in solution, and less difficulty in production, 49 which makes it a favorable candidate for functional modifications.…”
Section: Introductionmentioning
confidence: 99%